Role of serum renalase levels in predicting the presence of metabolic syndrome in patients with polycystic ovary syndrome - Burak Ersak; Gülnur Özakşit; Duygu Tugrul; Melike Doğanay; Yaprak Ustun; Mahmut Kuntay Kokanalı (Elsevier, 2023)
Objective: This study was designed to compare the serum renalase levels of polycystic ovary syndrome (PCOS) women with and without metabolic syndrome (MS) and those of healthy non-PCOS women. Materials and methods: Seventy-two patients diagnosed with PCOS and age-matched 72 healthy non-PCOS were included in the study. The PCOS group was divided into two groups as having metabolic syndrome or not. General gynecological and physical examination findings and laboratory results were recorded. Renalase levels in serum samples were determined using Enyzme-Linked ImmunoSorbent Assay method. Results: Mean serum renalase level was significantly higher in PCOS patients with MS compared with both PCOS patients without MS and healthy controls. Additionally, serum renalase correlates positively with body mass index, systolic and diastolic blood pressure, serum triglyceride and homeostasis model assessment-insulin resistance values among PCOS women. However, systolic blood pressure was found to be the only significant independent factor that can affect the serum renalase levels. A serum renalase level of 79.86 ng/L had a sensitivity of 94.7% and specificity of 46.4% in discriminating PCOS patients with metabolic syndrome from healthy women. Conclusions: Serum renalase level increases in women with PCOS in the presence of metabolic syndrome. Therefore, monitoring the serum renalase level in women with PCOS can predict the metabolic syndrome that may develop.